Memulihkan Kondisi Negara Pasca Pandemi Covid-19 pada Sektor Parawisata dalam Kegiatan Presidensi G20 - Aji, Wahyu Trisno (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This article explains Indonesia's golden opportunity as the host of the G20 Presidents event in 2021-2022 and the benefits and great opportunities for Indonesia in the tourism sector. This study uses a qualitative method with a literature study approach. The G20 is a cooperation forum consisting of 20 countries formed to discuss financial and non-financial issues such as anti-corruption, digitalization, and women's empowerment. The existence of this forum itself is very important for each member country, including Indonesia as one of the members of the G20 Presidents. Thus, the holding of the G20 Presidents forum in Indonesia is a great opportunity for the Indonesian nation to introduce Indonesia as widely as possible to other nations. Especially in the tourism sector, with the hope of showing the world that Indonesia is a nation that is very rich in various resources. So that it can be a great opportunity for Indonesia to cooperate with other countries for the benefit of its own country in the economic aspect after the Covid-19 pandemic.